The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/iju5.12290
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating penile injury due to the splintering of the floorboards in the gymnasium

Abstract: Introduction We present the case of a patient with penetrating penile injury caused by splintering floorboards in a gymnasium. Case presentation A 24‐year‐old man was brought to the emergency department of our hospital because of an unintentional penetrating penile injury sustained while playing volleyball at a gymnasium. He dove into the wooden floor to fly‐receive the ball. When sliding with his abdomen on the floor, a wooden splinter from the floorboard stuck from the base of his penis to near the glans pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The corpora, penile soft tissue or urethra can be involved in cases of penetrating penile injuries ( 11 ). Previous studies have indicated that up to 80% of penetrating penile injuries are accompanied by associated injuries, with the groin area and scrotum being the most commonly affects sites, followed by urethral injuries as the second most frequent occurrence ( 12 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The corpora, penile soft tissue or urethra can be involved in cases of penetrating penile injuries ( 11 ). Previous studies have indicated that up to 80% of penetrating penile injuries are accompanied by associated injuries, with the groin area and scrotum being the most commonly affects sites, followed by urethral injuries as the second most frequent occurrence ( 12 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Fortunately, this patient had normal erectile function after surgery. In addition, abdominal imaging should be performed as part of a complete trauma assessment in all patients with mechanical foreign body injuries where no associated primary injury is suspected ( 11 ). To this patient, an abdominal CT was performed immediately and successful indwelling catheterization was accomplished at the emergency room.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%